The Effect Of Competence, Work Stress, And Work Discipline On Employee Performance At PT Sawit Riau Makmur: The Effect Of Competence, Work Stress, And Work Discipline On Employee Performance At PT Sawit Riau Makmur - Novelia Anastasia; Harry Sanjaya; Leonardo Adyajaya; Vivi Angkasa; Sylvia Sylvia; Rahmat Alamsyah Harahap (Jurnal Mantik, 2020)
The purpose of this study is to analyze the effect of competence, work stress and work discipline on employees’ performances at PT Sawit Riau Makmur. The employees’ performances at PT Sawit Riau Makmur had experienced a decline due to lack of competence from the employees. The employees experienced work stress and poor work discipline. The population and samples in this study are amounted to 80 employees. The research method of this study is using multiple linear regression analysis method. The hypothesis test of this study is using partial test and simultaneous testing. The results of the coefficient of determination test obtained with value of 0.372which means 37.2% of the variation of the dependent variable namely employees’ performance that can be explained by variations in the independent variables which are competence, work stress and work discipline while the remaining 62.8% is explained by other variables not examined in this study. The conclusion of this study is work competency, work stress and work discipline simultaneously have a positive and significant effect towards employees’ performance at PT. Sawit Riau Makmur and work competence, work stress and work discipline partially have a positive and significant effect towards employees’ performance at PT. Sawit Riau Makmur.